Long-term sea level and climate variability at tide gauge stations: A study from Türkiye - Erkoc, Muharrem Hilmi; Dogan, Ugur (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study examines long-term sea level changes and their relationship with meteorological parameters at the Antalya, Bodrum, Erdek, and Mentes,tide gauge (TG) stations along the Mediterranean, Aegean, and Marmara coasts of T & uuml;rkiye between 1985 and 2024. Sea level trends were compared using both local TG data (TUDES) and satellite altimetry data from the Copernicus Marine Service (CMEMS). Trends in meteorological parameters were evaluated using parametric (least squares linear model) and non-parametric (Mann-Kendall trend test and Sen's Slope method) statistical analyses. The results indicate that the regional sea level rise rate for the period 1993-2024 was estimated at 3.3 +/- 1.0 mm/yr based on TG data and 3.8 +/- 0.7 mm/yr based on CMEMS data. Significant increases were observed in sea water temperature (0.035-0.051 degrees C/year) and air temperature (0.037-0.060 degrees C/year), while a statistically significant increase in water vapor pressure was only observed in Bodrum. Decreases were detected in atmospheric pressure and relative humidity; however, only the decline in relative humidity at Antalya was statistically significant. Autocorrelation analysis revealed periodic trends in sea level and meteorological observations, and cross-correlation analysis identified the lagged influence of thermal expansion and atmospheric pressure variations on sea level changes. This research is novel in employing the longest observational record for T & uuml;rkiye's coastal regions, combining in-situ and satellite-based data to provide timely insights into the coastal impacts of climate change.
Keywords: Sea level; Meteorological parameters; Hydro-geodesy; Tide gauge; Grid altimetry; SURFACE TEMPERATURE; MEDITERRANEAN SEA; ALTIMETRY; MOTION; TRENDS; LAND; RISE; Geochemistry & Geophysics; Meteorology & Atmospheric Sciences